Modelling strategies for assessing and increasing the effectiveness of new phenotyping techniques in plant breeding. (May 2019) - van Eeuwijk, Fred A.; Bustos-Korts, Daniela; Millet, Emilie J.; Boer, Martin P.; Kruijer, Willem; Thompson, Addie; Malosetti, Marcos; Iwata, Hiroyoshi; Quiroz, Roberto; Kuppe, Christian; Muller, Onno; Blazakis, Konstantinos N.; et al.
Highlights: We present various genotype to phenotype models to predict complex phenotypes with G×E as function of genotypic and environmental inputs. We show how genotype-to-phenotype models can be generalized to incorporate additional phenotypic information to improve yield predictions. We discuss how to evaluate the utility of information from new phenotyping techniques in the context of predictive genotype-to-phenotype models. Abstract: New types of phenotyping tools generate large amounts of data on many aspects of plant physiology and morphology with high spatial and temporal resolution. These new phenotyping data are potentially useful to improve understanding and prediction of complex traits, like yield, that are characterized by strong environmental context dependencies, i.e., genotype by environment interactions. For an evaluation of the utility of new phenotyping information, we will look at how this information can be incorporated in different classes of genotype-to-phenotype (G2P) models. G2P models predict phenotypic traits as functions of genotypic and environmental inputs. In the last decade, access to high-density single nucleotide polymorphism markers (SNPs) and sequence information has boosted the development of a class of G2P models called genomic prediction models that predict phenotypes from genome wide marker profiles. The challenge now is to build G2P models that incorporate simultaneously extensive genomic information alongside with new phenotypic information. Beyond the modification of existing G2P models, new G2P paradigms are required. We present candidate G2P models for the integration of genomic and new phenotyping information and illustrate their use in examples. Special attention will be given to the modelling of genotype by environment interactions. The G2P models provide a framework for model based phenotyping and the evaluation of the utility of phenotyping information in the context of breeding programs.